Global Financial Stability Report, April 2016 : Potent Policies for a Successful Normalization. (Global Financial Stability Report; Global Financial Stability Report ;, 2016)
The current Global Financial Stability Report (April 2016) finds that global financial stability risks have risen since the last report in October 2015. The new report finds that the outlook has deteriorated in advanced economies because of heightened uncertainty and setbacks to growth and confidence, while declines in oil and commodity prices and slower growth have kept risks elevated in emerging markets. These developments have tightened financial conditions, reduced risk appetite, raised credit risks, and stymied balance sheet repair. A broad-based policy response is needed to secure financial stability. Advanced economies must deal with crisis legacy issues, emerging markets need to bolster their resilience to global headwinds, and the resilience of market liquidity should be enhanced. The report also examines financial spillovers from emerging market economies and finds that they have risen substantially. This implies that when assessing macro-financial conditions, policymakers may need to increasingly take into account economic developments in emerging market economies. Finally, the report assesses changes in the systemic importance of insurers, finding that across advanced economies the contribution of life insurers to systemic risk has increased in recent years. The results suggest that supervisors and regulators should take a more macroprudential approach to the sector.